Incidence of congenital malformations and impact on the mortality of neonatal canines - Nobre Pacifico Pereira, Keylla Helena [UNESP] (2019)
Canine congenital malformations are structural or functional abnormalities of organs present at birth that possibly interfere with the viability of newborns, thus contributing to neonatal mortality. This study evaluated and described the incidence of congenital malformations in neonatal dogs and determined the mortality rates among those affected. Of the 178 litters and 803 newborns included in the study, 24.7% (44/178) of the litters presented neonates with congenital malformations. The total rate of neonates that presented malformations was 6.7% (64/803). The total mortality rate in newborns with congenital defects was 5.4% (44/803), representing 68.7% (44/64) of the deaths observed among those affected. The early (0–2 days old) and late (3–30 days old) mortality rates among the affected neonates were 61.4% (27/44) and 38.6% (17/44), respectively. In total, 27 malformations were recorded, and the most common congenital defects were cleft palate 2.8% (23/803) and hydrocephaly 1.5% (12/803), either alone or associated with other malformations. The malformations were recorded in 15 breeds: Pug, Miniature Pinscher, Rottweiler, Pitbull, French Bulldog, English Bulldog, Dachshund, Labrador Retriever, Lhasa Apso, Poodle, German Spitz, Yorkshire Terrier, Shih-tzu, Brazilian Terrier and mixed breed. One case of exposure to a teratogenic agent was reported, but no maternal exposure to teratogens during gestation was reported with the other litters. The occurrence of congenital defects may be related to genetic factors since the highest incidence of malformations (84.4%) was observed in purebred dogs.